Polycarbonate/silica nanocomposite membranes: Fabrication, characterization, and performance evaluation - Idris, A. (John Wiley and Sons Inc., 2017)
Polycarbonate/silica nanocomposite membranes at low silica loading were fabricated by solution blending and solvent evaporation technique. The functionalized silica nanoparticles used were synthesized by co-condensing hydrolyzed tetraethylorthosilicate with 3-aminopropyl trimethoxysilane in the sol–gel process. The membranes morphology, composition, surface, structure, thermal and mechanical properties were analyzed by the standard characterization techniques. The gas permeation tests were conducted in four-channel permeation cells. Field emission scanning electron microscopy results reveal that membranes above 3 wt silica content formed distinguishable voids and agglomerates. Fair distribution of silica nanoparticles and absence of residual solvents were observed by energy dispersive X-ray and thermogravimetric analysis. Fourier transform infrared spectroscopy spectra confirmed the presence of new functional groups (NH) and (OH) bonds. The X-ray diffraction pattern revealed the polymer-particle interactions, the formation of rigidified polymer chain, and nanostructured silicon crystals. Further, the thermogravimetric analysis results revealed thermal stability enhancement while differential scanning calorimetry results of increased glass transition temperatures confirmed the presence of rigidified polymer chain. Furthermore, enhancements in mechanical strength of the membranes were observed. Moreover, at all feed pressures, increased CO2, N2, and CH4 gas permeation was observed. At 6 bar feed pressure, the CO2/N2 and CO2/CH4 ideal selectivities of PC membranes with 3 wt silica loading have increased from 19.2 to 38.0 and 29.2, respectively. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45310. © 2017 Wiley Periodicals, Inc.